Pelatihan Membaca Tanpa Mengeja untuk Meningkatkan Kompetensi Mengajar Membaca Permulaan Mahasiswa S1 PGSD - Warikar, Amelia; Septikasari, Dian (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Early reading instruction in elementary schools still faces challenges, particularly due to the widespread use of spelling-based methods that hinder holistic word recognition. This issue is also prevalent among PGSD (Primary School Teacher Education) students at Cenderawasih University, who as prospective teachers lack effective strategies for teaching beginning reading. To address this, a participatory training program was designed, consisting of lectures, demonstrations, simulations (microteaching), and reflection. This community service activity involved 30 undergraduate PGSD students selected through proportional sampling. Evaluation was conducted using pre-test and post-test instruments (20 validated multiple-choice questions) and observation sheets for teaching skills. Quantitative analysis included percentage increase, N-Gain, and paired t-test for statistical significance. The results showed an average increase of 55.1% (pre-test mean = 54.2, post-test mean = 84.3), with an N-Gain score of 0.67 (moderate-to-high category). The paired t-test yielded a significant difference (t(29) = 12.45, p < 0.001). Students also demonstrated improved method application, use of instructional media, and teaching confidence. However, this training was limited by its short duration (12 hours) and lack of direct implementation in real elementary school classrooms. Therefore, future activities should include field practice and ongoing mentoring to ensure sustainable impact.